2019
DOI: 10.1097/ta.0000000000002067
|View full text |Cite
|
Sign up to set email alerts
|

Impact of licensed federal firearm suppliers on firearm-related mortality

Abstract: BACKGROUND Legal firearm sales occur largely through suppliers that have Federal Firearm Licensees (FFLs). Since FFL density might reflect ease-of-access to firearm purchases, we hypothesized that the number of FFL dealers would be associated with firearm-related deaths. We further hypothesized that licensee-type subsets would be associated with differential risks for gun-related deaths. METHODS We used data from the National Center for Health Statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…The per capita number of licensed gun dealers, obtained from U.S. Bureau of Alcohol, Tobacco, Firearms and Explosives, 25 and the percentage of the hunting license holder of the state's population, obtained from the National Survey of Fishing, Hunting, and Wildlife-Associated Recreation, 26 were included as proxy controls for household gun ownership. 3,27,28 As a further proxy measure for state sentiment toward firearm control, the vote share differences between the Republican and Democratic presidential candidates in each presidential election year within the study period 29 were included and extrapolated for years between presidential elections.…”
Section: Methodsmentioning
confidence: 99%
“…The per capita number of licensed gun dealers, obtained from U.S. Bureau of Alcohol, Tobacco, Firearms and Explosives, 25 and the percentage of the hunting license holder of the state's population, obtained from the National Survey of Fishing, Hunting, and Wildlife-Associated Recreation, 26 were included as proxy controls for household gun ownership. 3,27,28 As a further proxy measure for state sentiment toward firearm control, the vote share differences between the Republican and Democratic presidential candidates in each presidential election year within the study period 29 were included and extrapolated for years between presidential elections.…”
Section: Methodsmentioning
confidence: 99%
“…Our hypothesis that FFL openings would lead to increases in firearm self-harm was based on prior studies that identified positive associations of firearm dealer density with firearm suicide, homicides, robberies, gun-related crimes, and firearm ownership [17][18][19][20][21][22][23]. However, there are several important differences between these studies and our approach.…”
Section: Plos Onementioning
confidence: 99%
“…To our knowledge, only one previous study has examined firearm dealers and self-harm. Chao and colleagues found a positive association of state-level firearm dealer density with firearm suicides [17], while Price et al found no association [18]. Local-level firearm dealer proximity or density, which are more likely to shape behavior, and nonfatal firearm self-harm injuries remain unexamined.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations